POLA ASUH KELUARGA BURUH TANI TERHADAP ANAK REMAJANYA DI KELURAHAN MUARA MULIA KECAMATAN TANAH JAWA KABUPATEN SIMALUNGUN SUMATERA UTARA - Marpaung, Astina Hotnauli; Sumardi, Sumardi; Ayub, Daeng (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the most dominant parenting pattern applied by the family of farm laborers to their adolescent children in Muara Mulia Village, Tanah Java Sub-district, Simalungun Regency, North Sumatra. The benefit of this research is to give thought contribution to the family who work as parent farm laborers who work as farm laborers in applying parenting to take care of their children to become the generation that boast of nation, homeland, family and society. This study is also useful as a comparison material for other researchers who will conduct research in the same field. This research is descriptive with quantitative approach. The sampling technique used in this study is Proportional Stratified Random Sampling because this study has a stratified population in proportion to the theoretical basis according to Sugiyono. Instrument in this research is by questionnaire which amounts to 60 items statement about the pattern of foster farming family's families to their adolescent children in Muara Mulia Village, Tanah Jawa Sub-district, Simalungun Regency, North Sumatra, with indicators of democratic parenting, authoritarian parenting and permissive parenting. The result of data analysis shows that permissive parenting pattern is more dominantly applied by farmer's family to their adolescent children in Muara Mulia Sub-district, Tanah Jawa Sub-district, Simalungun Regency, North Sumatera. It is seen from the mean and SD which are high, that is mean 3.77 and SD 0,57 compared to democratic parenting and authoritarian parenting.Key Words: Parenting, Farm workers, Muara Mulia Districts